O estudo do meio no ensino de geografia: um caminho para discussão dos problemas ambientais do município de João Pessoa - Lima Junior, Guibson da Silva (2014)
This work, divided into four items, aimed at proposing itineraries for field classes, as a step of environmental study, whose the generator theme focused on environmental problems. The first item sought to characterize of the studied area - the city of João Pessoa - through discussion related to its urban sprawl and the exposure of its natural features. In the second item were exposed the methodological procedures used for the preparation of research and the theoretical axes that justify it. This way, the social issues highlight as essential to the understanding of environmental issues in the cities. Still on this item, another important discussion was performed in order to demonstrate different offers of extra room activities, emphasizing the environmental study as an interdisciplinary practice and its importance for grasping reality. In the third item, we carried out a questionnaires analysis applied to Geography teachers of Middle schools located in the Polo I in the city of João Pessoa. That way, the objective was to understand how local environmental problems are being addressed in geography lessons in basic education. Qualitative analysis of the data resulting from application of these questionnaires provided, among other things, to understand the main barriers encountered in conducting field activities, as well greatest relevance environmental problems. Finally, the fourth item, three scripts were submitted for field classes, as a step of environmental study, which aims to contribute to the understanding of local environmental issues, being discussed the characteristics of some areas in João Pessoa which are characterized by the presence of important social environmental issues, revealed as marks of the urban sprawl process of the city.